Effects of national development projects on food security : a case of Tokwe-Mukosi dam - Masocha, Jerrphanos (BUSE, 2019)
The study focuses on the effects of national development projects on food security in the context of local communities living adjacent to the development site. It focused on Tokwe-Mukosi Dam construction project in Masvingo province in Zimbabwe. The dam is the largest inland dam in the country. The dam project physically and economically displaced a significant proportion of people who lived in its basin. The study adopted the analytical descriptive approach to demonstrate the existence of socio-economic problems on livelihood and food security issues. These issues are explored in two papers in this thesis. The first paper assesses the effect of dam construction on livelihoods of local communities. Specifically, the paper assesses livelihoods before and after dam Tokwe-Mukosi dam construction. Statistical significance of livelihoods before and after dam construction was justified by use of McNemar test for correlated proportions. The results show that there is a significant difference between livelihoods before and after the dam construction. The second paper assesses the food security situation of households affected by the dam project. To achieve this objective, the paper used the Household Food Insecurity Access Scale tool for assessing food insecurity (access). Household Food Insecurity Access Scale prevalence calculated results show that the affected households were food insecure. A statistical test was then performed for independence between household settlement and food security status using Fisher‟s exact test for independence. Results have shown statistically significant difference of p<.01 concluding that there is an association between respondent‟s settlement and his or her food security status. The results of this study help to shed light on the link between national development projects and food security of the affected communities. It has been concluded that national development projects negatively affect livelihood strategies of local communities. There is therefore need to design policies that increase communities‟ adaptive capacity and increase local food production while providing food assistance as a stop gap measure. Keywords: Livelihood, Community, Household, Development, food security
Keywords: National development projects; Food security